Pengembangan Potensi Kawasan Pesisir Kota Makassar Sebagai Objek Wisata Berdasarkan Preferensi Pemangku Kepentingan (Stakeholder) - Ferdiansyah Ferdiansyah; Slamet Trisutomo; Venny Veronica Natalia (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2016)
The purpose of this research is to identify the potential of the coastal tourism area of ​​Makassar City, determine stakeholder preferences related to the development of tourism potential and determine the direction of developing coastal tourism potential based on stakeholder preferences. The research location is divided into four tourist spots based on the direction of Makassar City RTRW in 2010-2030 along the Makassar City coast with integrated business and tourism development functions. In the study the tourist areas are along the coast of Makassar City namely Tanjung Layar Putih Beach, Tanjung Bayang, Akkarena, Losari, and Paotere Harbor. The sampling method used was purposive sampling by taking data in the form of distributing questionnaires specifically divided into four coastal tourism spots in Makassar City. The analysis technique used is descriptive qualitative quantitative and importance performance analysis. The results showed that the tourism potential in each tourist spot in the form of attractions, facilities, and accessibility of tourism that can be developed. Preparation of directions for stakeholder preferences based on development in each of the spot spots I, II, and III, namely, an increase in special interest tours such as water sports and fishing, increased parking, provision of tourist service facilities such as gazebos and rest areas, toilet and water maintenance clean, providing public transportation and pedestrian paths. Spot IV direction is to improve the quality of special interest tours such as PPI and culinary tourism, the provision of tourist facilities such as gift shops and public transportation.